Quality Versus Equality. The Integration as the Component of Primarly School’s Excellence – a Cross-Cultural Perspective - Zolnai, Erika; Hüse, Lajos; Balogh, Erzsébet; Farnicka, Marzanna; Holecek, Vaclav (Przegląd Badań Edukacyjnych (Educational Studies Review), 2017)
This study is about the continuous flaring debate how to measure the school’s performance, how the integration efforts will be equivalent in addition to the absolute value of student performance. Contributors analyzed the international processes which determine the role of public education and its effectiveness both internationally and with special focus on Hungary. Authors tried to emphasize local characteristics and highlight how globalization processes are suitable for the performance of schools in V4 countries. In the article, there was also given a description of the paradigm shift in the Hungarian educational system and the role of the inclusive integrated school in the framework of Hungarian integration efforts. This Hungarian framework was compared with Polish, Czech and Slovak solutions. This work could be instructive for educators based on the historical and societal similarities of these four countries.